KINERJA KEUANGAN DAN NILAI PASAR PERUSAHAAN ROKOK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Maria Lidiana Belak; Octovianus Nawa Pau; Christien C. Foenay (Universitas Nusa Cendana, 2018)
This study aims to explain the Financial Performance (Current Ratio, Total Asset Turnover, DebtTo Equity Ratio, Return On Asset) and Market Value of the company (Earning Per Share) in thetobacco industry listed on the Indonesia Stock Exchange period 2012-2016. This research describesthe company financial condition through a quantitative approach in the form of Financial Ratiosand Market Value. Financial Performance is viewed from (1) Current Ratio for PT. GudangGaram, Tbk (GGRM) and PT. Bentoel International Investama, Tbk (RMBA) are not liquid.While PT. Handjaya Mandala Sampoerna, Tbk (HMSP) is in a liquid condition (2) TotalAsset Turnover PT. Gudang Garam, Tbk (GGRM) and PT. Bentoel International Investama, Tbk(RMBA) are in an inefficient category. While PT. Handjaya Mandala Sampoerna, Tbk (HMSP) isin the efficiency category. (3) Debt To Equity Ratio for tobacco companies are in the solvablecategory. (4) Return on Asset PT. Gudang Garam, Tbk and PT. Bentoel International Investama,Tbk (RMBA) are in the category not efficient. While PT. Handjaya Mandala Sampoerna, Tbk isin the efficiency category. (5) Earning per Share PT. Gudang Garam, Tbk (GGRM) and PT.Handjaya Mandala Sampoerna, Tbk (HMSP) are in the good category. While PT. BentoelInternational Investama, Tbk (RMBA) is in the not very good category.Keyword : Current Ratio, Debt To Equity Ratio, Earning Per Share, Return On Asset, Total AssetTun Over